Calcite-saturated natrocarbonatites: composition, crystal morphology, and weathering - Anenburg, Michael; Aslam, Izzan Nur (Volcanica, 2024)
Interpretation of calcite-dominated fossil carbonatite volcanoes is complicated by the instability of many igneous carbonatite materials on Earth’s surface. One hypothesis suggests that they originate by eruption of alkali-free calcic carbonatite lavas. However, liquid calcite is not thermodynamically stable at atmospheric pressure. A second hypothesis suggests that calcite is secondary and formed after primary nyerereite lost its alkalis to surface water. Here, we experimentally test a combined hypothesis in which solid calcite phenocrysts are suspended in natrocarbonatite lava that solidifies primarily to nyerereite, and determine calcite solubilities in sodic carbonate liquids. Then, we dissolve alkalis in water over several months to show formation of secondary calcite after nyerereite. Textural and geochemical observations from our experiments are consistent with many natural volcanic carbonatites, suggesting that alteration of initially calcite–nyerereite-bearing natrocarbonatites to pure calcite carbonatites was common in Earth’s geological past.